Auctioning Off Budgets in Procurement - Claudio Rottner (The RAND Journal of Economics, 2025)
This article investigates a multi-unit pay-as-bid procurement auction where the auctioneer fixes total spending and maximizes the quantity procured with their predetermined, secret budget. Previous literature has analyzed fixed-quantity auctions, where the traded quantity is fixed but unknown to the bidders. Compared to such auctions, budget auctions lower the auctioneer's costs by introducing an additional interaction between a bidder's bids; bidders not only weigh a higher profit margin on a unit against a lower probability of supplying that unit; a higher margin on some unit also reduces the probability that the budget suffices to procure more units from the~bidder.
Keywords: 330; reverse auction; multi-unit auction; procurement; pay-as-bid